The Outlook of Brazilian Amazon Forest Restoration under The Leadership of President Lula da Silva - Numadi, Katong Ragawi (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2024)
The implementation of anti-environmental policies during the conservative government under President Jair Bolsonaro has resulted in the destruction of the Brazilian Amazon forest region. The deforestation rate, which had previously decreased, started to climb significantly in 2019. The devastating forest fires that hit the Amazon at the end of this year is indivisible from the government's neglect. The re-election of Lula da Silva as President of Brazil in 2023 sparked great optimism among the Brazilians and international public for restoring Brazilian Amazon forestbecause Lula, as Brazil president for two previous periods, had succeeded in reducing the deforestation and destruction of the Brazilian Amazon forest to its lowest point in 2003-2011. Therefore, this paper aims to examine the vision of restoring the Brazilian Amazon forest under the new government of Lula da Silva. This study uses a qualitative method that relies on various information originating from government documents, related books and journals, online news reports, and several other types of secondary data. Based on the initial research, Lula has carried out multiple programs related to Amazon Forest restoration, from initiating sustainable economic development to strengthening law enforcement, protecting indigenous communities, and strengthening cooperation with the international community. As a result, the level of deforestation and forest fires in the Amazon has now followed a significant downward trend. Keywords: Amazon, Brazil, Lula da Silva